Development of a Simple Fe(II) Ion Colorimetric Sensor from the Immobilization of 1,10-Phenanthroline In Alginate/Pectin Film - Nindya Tri Muliawati; Dwi Siswanta; Nurul Hidayat Aprilita (Universitas Gadjah Mada, 2021)
An optical analytical sensor was proposed based on the complexation reactions of 1,10-phenanthroline derivative in aqueous solutions. This study aims to synthesize a metal ion sensor for detecting Fe(ll) ion from the immobilization of 1,10-phenanthroline compound in alginate/pectin film. This was carried out by characterizing the films using the Fourier-transform infrared spectrometry (FT-IR) and scanning electron microscope (SEM). The determination of the optimal condition for Fe(II) ion detection and validation of the parameters was conducted by measuring the absorbance of the films using a UV-Vis spectrophotometer. After the addition of Fe(II) ion, the color of the alginate/pectin-phenanthroline film changed from transparent yellow to orange-red, showing its potential as a visual colorimetric sensor for iron(II) ion. It was found that the optimum condition for Fe(II) ion sensing was at 513 nm after 2 min of detection at pH 2. The alginate/pectin-phenanthroline film had good linearity, precision, selectivity, and accuracy with a detection limit as low as 0.446 mg L–1, which was remarkable.